Establishment of the uterine microbiome following artificial insemination in virgin heifers - Moraes, Joao G. N.; Gull, Tamara; Ericsson, Aaron C.; Poock, Scott E.; Caldeira, Monica O.; Lucy, Matthew C. (Frontiers in Microbiology, 2024)
A sterile uterus was challenged by recent studies that have described the microbiome of the virgin and pregnant uterus for species including humans and cattle. We designed two studies that tested whether the microbiome is introduced into the uterus when the virgin heifer is first inseminated and whether the origin of the microbiome is the vagina/cervix.The uterine microbiome was measured immediately before and after an artificial insemination (AI; Study 1; n = 7 AI and n = 6 control) and 14 d after insemination (Study 2; n = 12 AI and n = 12 control) in AI and non-AI (control) Holstein heifers. A third study (Study 3; n = 5 Holstein heifers) that included additional negative controls was subsequently conducted to support the presence of a unique microbiome within the uterus despite the low microbial biomass and regardless of insemination. Traditional bacteriological culture was performed in addition to 16S rRNA gene sequencing on the same samples to determine whether there were viable organisms in addition to those detected based on DNA sequencing (16S rRNA gene sequence).Results and discussion: Inseminating a heifer did not lead to a large change in the microbiome when assessed by traditional methods of bacterial culture or metataxonomic (16S rRNA gene) sequencing (results of Studies 1 and 2). Very few bacteria were cultured from the body or horn of the uterus regardless of whether an AI was or was not (negative control) performed. The cultured bacterial genera (e.g., Bacillus, Corynebacterium, Cutibacterium, Micrococcus, Staphylococcus, and Streptococcus) were typical of those found in the soil, environment, skin, mucous membranes, and urogenital tract of animals. Metataxonomic sequencing of 16S rRNA gene generated a large number of amplicon sequence variants (ASV), but these larger datasets that were based on DNA sequencing did not consistently demonstrate an effect of AI on the abundance of ASVs across all uterine locations compared with the external surface of the tract (e.g., perimetrium; positive control samples for environment contamination during slaughter and collection). Major genera identified by 16S rRNA gene sequencing overlapped with those identified with bacterial culture and included Cutibacterium, Staphylococcus, and Streptococcus.